Educational Management Strategies to Develop Financial Resources, Competence, and Business Growth Capabilities of Small Enterprises Operated by Housewives in Kota Pari Village - Rahayu, Sri; Faried, Annisa; Sembiring, Rahmad; Sumaya, Sumaya; Kimpah, Jeniboy (IJORER : International Journal of Recent Educational Research, 2025)
Objective this study aims to examine how educational management strategies influence the development of financial resource utilization, entrepreneurial competence, and business growth in MSMEs operated by housewives in Kota Pari Village. We sought to identify the most effective educational approaches to enhance rural women entrepreneurs' ability to sustain and expand their businesses despite limited resources and traditional constraints. Method a sequential mixed-methods approach was employed, beginning with quantitative data collection through structured questionnaires distributed to 200 MSME operators using Google Forms. This was followed by in-depth interviews with 30 purposively selected participants. Six focus group discussions (FGDs) with village officials and MSME stakeholders provided additional contextual insights. Quantitative data analysis used path analysis, while qualitative data were analyzed through thematic coding and triangulation to ensure validity. Results educational management interventions significantly affected business success (R² = 0.487; p < 0.001), both through direct pathways (β = 0.342; p < 0.001) and indirect effects mediated by entrepreneurial capability development (β = 0.305; p < 0.001) and improved capital management (β = 0.253; p < 0.001). Relationship-based educational approaches, particularly mentorship programs (β = 0.412; p < 0.001), demonstrated superior effectiveness compared to traditional instructional methods. Contextually relevant educational content focusing on immediate business challenges was shown to have much higher implementation rates than generic business training. Novelty this research is one of the first to empirically explore educational management in the context of rural women entrepreneurship in Indonesia. We uncover previously undocumented barriers to educational effectiveness for rural women entrepreneurs and provide a contextually grounded framework for designing educational interventions that are better adapted to the social and economic realities of housewife-operated enterprises in Indonesia's developing rural economy.